The Effect Of Green Product And Green Advertising On He Purchase Decision Of Drinking Water In The Kitaro Brand On The Community Of Pondok Kelapa District, Bengkulu Central Bengkulu - Kusnadi, Deky; Soleh, Ahmad; Irwanto, Tito (Social Sciences Journal, 2024)
The green marketing or go green campaign program in Indonesia is shown by the development of environmentally friendly products (green products) by the industry to attract consumers to make purchases. The purpose of this study was to determine the effect of green advertising and green products on purchasing decisions of drinking water in the KitaRO brand in the community of Pondok Kelapa District, Central Bengkulu Regency. The sample in this study was 100 people from Pondok Kelapa District, Central Bengkulu Regency who purchased KitaRO bottled drinking water. Collecting data using a questionnaire and the analytical method used is multiple linear regression, determination test and hypothesis testing. The results of the regression analysis show Y = 7.153 + 0.282X1 + 0.562 X2, this describes a positive regression direction, meaning that there is a positive influence between X1 (Green product) and X2 (green advertising) on purchasing decisions (Y). It means that if the Green product and green advertising variables increase, it will increase purchasing decisions. The magnitude of the coefficient of determination is 0.390. This means that X1 (Green product) and X2 (green advertising) affect purchasing decisions (Y) by 39% while the remaining 61% is influenced by other variables not examined in this study. The results of the t-test at a significance level of 0.05 explain that partially the Green product and green advertising variables have a significant influence on the variable purchasing decisions of drinking water in the KitaRO brand in the community of Pondok Kelapa District, Central Bengkulu Regency. The results of the F test at a significance level of 0.05 explains that the Green product and green advertising variables have a simultaneous (together) influence on the decision to purchase KitaRO branded drinking water in the community of Pondok Kelapa District, Central Bengkulu Regency